Corrosion resistance of mild steel immersed in simulated concrete pore solution in the presence of sodium potassium tartrate - Pushpa Murugesh; Veerapandian Velkannan; Gurmeet Singh; Hashem Abdulhameed Al; Susai Rajendran; Arjunan Krishnaveni (Zaštita Materijala)
The corrosion resistance of mild steel in simulated concrete pore solution (SCPS) in the absence and presence of sodium potassium tartrate (SPT) has been investigated by polarization technique and AC impedance spectra. The present study leads to the following conclusions. Polarization study reveals that sodium potassium tartrate system functions as anodic type of inhibitor. AC impedance spectra reveal that a shielding film is formed on the metal surface. When mild steel is used as rebar, sodium potassium tartrate may be mixed with concrete. Thus the mild steel will be protected from corrosion. The protective film consists of ferrous tartrate complex formed on metal surface. In the presence of sodium potassium tartrate the linear polarisation resistance increases from 226 Ohmcm2 to 455 Ohmcm2 , corrosion current decreases from 1.901x10-4A/cm2 to1.096 x10-4A/cm2 , charge transfer resistance (Rt) increases from 49 Ohmcm2 to 77 Ohmcm2 , impedance increases from 1.807 to 2.084, phase angle increases from 33.92° to 35.31° and double layer capacitance (Cdl) value decreases from 1.040x10-7 F/cm2 to 0.662 x10-7 F/cm2 . Corrosion potential shifts from -973 mV/SCE to -867 mV/SCE .This confirms that the inhibitor system functions as anodic type of inhibitor controlling anodic reaction predominantly. This formulation may find application in concrete technology. This may be used in the construction of bridges and concrete structures.